Area Development Strategy to Overcome the Slumps in RW 3 and RW 5, Polehan Village, Blimbing, Malang, Using IFAS and EFAS Matrix Analysis - Dhari, Leonardus Fasiusta (Journal of International Conference Proceedings, 2020)
The purpose of this study is determining significant factors to overcome slum areas using IFAS and EFAS matrix. IFAS (Internal Factor Analysis Summary) matrix was used to analyze internal factors, including strengths and weaknesses, and EFAS (External Factor Analysis Summary) matrix was used to analyze external factors in the research area. The methodological approach in this study was qualitative which is descriptive redundant. The research was conducted at slum area of RW III and RW V, Polehan Village, Blimbing District, Malang City. The data were collected by field observations, in-depth interviews, documentation and data triangulation. The results of the analysis showed that there was a reduction in the strength and weakness values which are -1.883 (negative) and the opportunity and threat values are 0.333 (positive). These values are in quadrant II of room D in the form of selective maintenance strategy. The formulated strategy is to improve the quality of human resources (HR) in handcrafting sector by increasing the intensity of training and adding home industries, joint fund management, savings and loans as capital for households to develop Small and Medium Enterprises and increase community participation in supporting planning activities as well as institutional activities.